Quantification of Acetabular Coverage on 3-Dimensional Reconstructed Computed Tomography Scan Bone Models in Patients With Femoroacetabular Impingement Syndrome: A Descriptive Study. Issue 11 (9th November 2021) - DeFroda, Steven F.; Alter, Thomas D.; Lambers, Floor; Malloy, Philip; Clapp, Ian M.; Chahla, Jorge; Nho, Shane J.
Background: Accurate assessment of osseous morphology is imperative in the evaluation of patients with femoroacetabular impingement syndrome (FAIS) and hip dysplasia. Through use of computed tomography (CT), 3-dimensional (3D) reconstructed hip models may provide a more precise measurement for overcoverage and undercoverage and aid in the interpretation of 2-dimensional radiographs obtained in the clinical setting. Purpose: To describe new measures of acetabular coverage based on 3D-reconstructed CT scan bone models. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Preoperative CT scans were acquired on the bilateral hips and pelvises of 30 patients before arthroscopic surgical intervention for FAIS. Custom software was used for semiautomated segmentation to generate 3D osseous models of the femur and acetabulum that were aligned to a standard coordinate system. This software calculated percentage of total acetabular coverage, which was defined as the surface area projected onto the superior aspect of the femoral head. The percentage of coverage was also quantified regionally in the anteromedial, anterolateral, posteromedial, and posterolateral quadrants of the femoral head. The acetabular clockface was established by defining 6 o'clock as the inferior aspect of the acetabular notch. Radial coverage was then calculated along the clockface from the 9-o'clock to 5-o'clock positions. Results: The study included 20 female and 10 male patients with a mean age of 33.6 ± 11.7 years and mean body mass index of 27.8 ± 6.3. The average percentage of total acetabular coverage for the sample was 57% ± 6%. Acetabular coverages by region were as follows: anteromedial, 78% ± 7%; anterolateral, 18% ± 7%, posterolateral, 33% ± 13%, and posteromedial, 99% ± 1%. The acetabular coverage ranged from 23% to 69% along the radial clockface from 9 to 5 o'clock. Conclusion: This study demonstrated new 3D measurements to characterize acetabular coverage in patients with FAIS and elucidated the distribution of acetabular coverage according to these measurements.